ICTV Virus Taxonomy Profile: Caulimoviridae. (17th October 2020) - Teycheney, Pierre-Yves; Geering, Andrew D. W.; Dasgupta, Idranil; Hull, Roger; Kreuze, Jan F.; Lockhart, Ben; Muller, Emmanuelle; Olszewski, Neil; Pappu, Hanu; Pooggin, Mikhail M.; Richert-Pöggeler, Katja R.; Schoelz, James E.; et al.
Abstract : Caulimoviridae is a family of non-enveloped reverse-transcribing plant viruses with non-covalently closed circular dsDNA genomes of 7.1–9.8 kbp in the order Ortervirales . They infect a wide range of monocots and dicots. Some viruses cause economically important diseases of tropical and subtropical crops. Transmission occurs through insect vectors (aphids, mealybugs, leafhoppers, lace bugs) and grafting. Activation of infectious endogenous viral elements occurs in Musa balbisiana, Petunia hybrida and Nicotiana edwardsonii . However, most endogenous caulimovirids are not infectious. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Caulimoviridae, which is available at ictv.global/report/caulimoviridae .